Leap over a wall earthly spirituality for everyday Christians - Peterson, Eugene H., 1932- (San Francisco, CA Harper, 1997)
Includes bibliographical references.
Keywords: David, King of Israel; Bible. O.T. Samuel, 1st, XVI - Kings, 1st, II -- criticism, interpretation, etc; Bible. O.T. -- biography